2020
DOI: 10.3390/electronics9081317
|View full text |Cite
|
Sign up to set email alerts
|

Lexicon-based Sentiment Analysis Using the Particle Swarm Optimization

Abstract: This work belongs to the field of sentiment analysis; in particular, to opinion and emotion classification using a lexicon-based approach. It solves several problems related to increasing the effectiveness of opinion classification. The first problem is related to lexicon labelling. Human labelling in the field of emotions is often too subjective and ambiguous, and so the possibility of replacement by automatic labelling is examined. This paper offers experimental results using a nature-inspired algorithm—part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Effectivity of lexicon approach, of course depends on the correct choice of words in the lexicon and their most accurate assessing with the degree of polarity. In our work [ 29 ] the effective lexicon-based application for sentiment analysis is described. For this application two lexicons were generated-Big and Small.…”
Section: Methodsmentioning
confidence: 99%
“…Effectivity of lexicon approach, of course depends on the correct choice of words in the lexicon and their most accurate assessing with the degree of polarity. In our work [ 29 ] the effective lexicon-based application for sentiment analysis is described. For this application two lexicons were generated-Big and Small.…”
Section: Methodsmentioning
confidence: 99%
“…The sentiment scores of common words can be obtained from a lexicon (Musto et al 2015). The problem with the lexicon-based approach is that sentiment of sentences or texts which do not contain words from the lexicon cannot be successfully classified (Machová et al 2020). The degree of applicability of the lexicon to the text therefore determines the effectiveness of the lexicon-based approach.…”
Section: Methodsmentioning
confidence: 99%
“…Their study showed sentiment classification system with 92% accuracy. Machová et al (2020) used lexicon and Naïve Bayes to solve SA problem. They employed particle swarm optimization (PSO) for automatic labelling of words to develop their lexicon.…”
Section: Hybrid Approachmentioning
confidence: 99%